Conteúdos digitais para o tema ondulatória na proposta curricular do Estado de São Paulo - Magalhães, Arthur Alexandre (2014)
This work proposes digital content for the Waves theme which can be inserted into the curriculum of the State of São Paulo. Technologies are part of the daily lives of students, and can be used as motivational tools in the teaching-learning process. Digital content consists of learning objects, such as videos, audios and simulations, accompanied by activities that provide an active student participation in the teachinglearning process. Activities were inspired by research methodology and have different levels of freedom, i.e. varying degrees of teacher intervention. We conclude that the activities with greater student autonomy lead to a more meaningful concept learning. It is noteworthy that, in addition to the positive result, this work has produced a considerable change in my teaching practice as I started to develop activities with investigative approach, in which the student carries out the process of knowledge construction.